THE DEVELOPMENT OF ‘SNAKE AND LADDER’ LEARNING MEDIA TO ENRICH INDONESIAN VOCABULARY IN THEMATIC INSTRUCTIONFOR FOURTH GRADE STUDENTS - Pratiwi, Yohana Intan; Nusarastriya, Haris (International Journal of Elementary Education, 2017)
This research method used was Research and Development (RnD) by adapting the research and development steps by Borg and Gall. This research aims to help fourth grade students to enrich their Indonesian vocabulary, and also to know the validity, effectiveness, and practicality of the developed product. The developed product was ‘snake and ladder’ learning media with 31 grade four students of SD Negeri 02 Bringin as the subjects of this research. The data collection technique in this research used test (evaluation questions) and non-test (observation, questionnaire, and documentation). The validity of the product was analyzed from the calculation of media and material expert test, whereas the effectiveness was analyzed using Paired-Sample T Test with SPSS program. The practicality of the media was analyzed from the result of the observation and questionnaire from teachers and students. From this research, it can be concluded that ‘snake and ladder’ learning media to enrich the students’ Indonesian vocabulary in thematic instruction was proven as valid, effective, and practical. The validity was proven with the average score 4,90 (very good) by the media expert and 4,00 (good) by the material expert. The effectiveness of the product was proven by significance score which showed that the result of two evaluation tests, which were X1 (implementation of snake and ladder which has not been developed) and X2 (implementation of developed product), was significant with the amount 0,000, and also 61% students got above average grade which was 86,93. The practicality proof came from the teacher observation with the average score 5,00 (very good) and the questionnaire of students and teacher toward the developed product with the average score 4,94 (very good) and 5,00 (very good)